Percutaneous dilatation tracheostomy at liver transplantation intensive care unit by surgeons (Annals of Medical Research, 2021)
Aim: Tracheostomy has evolved to be a routine procedure for prolonged mechanical ventilation patients in the intensive care unit. We aimed to analyze retrospectively our patients underwent percutaneous dilatation tracheostomy due to prolonged mechanical ventilation following liver transplantation.Material and Methods: Data of 34 patients who underwent percutaneous dilatation tracheostomy by general surgeons due to prolonged mechanical ventilation following liver transplantation were analyzed and evaluated retrospectively.Results: Patients did not experience any complications except minor bleeding following liver transplantation. Besides this technique facilitated patient compliance as well as comfort, which were essential during an accurate weaning process.Conclusion: Percutaneous dilatation tracheostomy is a safe method due to its low complication rate and easy applicability in hands of surgeons who are familiar with the neck anatomy.
Keywords: Tracheostomy; intensive care unit liver transplantation